Aluminium trihydroxide in combination with ammonium polyphosphate as flame retardants for unsaturated polyester resin (eXPRESS Polymer Letters)
The thermal and reaction to fire characteristics of a flame retardant unsaturated polyester (UP) ternary system are presented here. Thermal gravimetric analysis showed an improved thermal stability between 200–600°C with the addition of ammonium polyphosphate (APP) and aluminium trihydroxide (ATH) formulation. Cone calorimetry tests indicated that ATH is more efficient than calcium carbonate at delaying the ignition time, lowering the carbon monoxide yield and lowering the peak heat release (PHRR). However the addition of APP and ATH to the formulation failed to demonstrate any significant synergistic effect at reducing the PHRR.